Diverse antitumor effects of ascorbic acid on cancer cells and the tumor microenvironment - Maekawa, Takeru; Miyake, Toru; Tani, Masaji; Uemoto, Shinji (Frontiers in Oncology, 2022)
Ascorbic acid has attracted substantial attention for its potential antitumor effects by acting as an antioxidant in vivo and as a cofactor in diverse enzymatic reactions. However, solid proof of its clinical efficacy against cancer and the mechanism behind its effect have not been established. Moreover, cancer forms cancer-specific microenvironments and interacts with various cells, such as cancer-associated fibroblasts (CAFs), to maintain cancer growth and progression; however, the effect of ascorbic acid on the cancer microenvironment is unclear. This review discusses the effects and mechanisms of ascorbic acid on cancer, including the role of ascorbic acid concentration. In addition, we present future perspectives on the effects of ascorbic acid on cancer cells and the CAF microenvironment. Ascorbic acid has a variety of effects, which contributes to the complexity of these effects. Oral administration of ascorbic acid results in low blood concentrations (<0.2 mM) and acts as a cofactor for antioxidant effects, collagen secretion, and HIFα degradation. In contrast, intravenous treatment achieves large blood concentrations (>1 mM) and has oxidative-promoting actions that exert anticancer effects via reactive oxygen species. Therefore, intravenous administration at high concentrations is required to achieve the desired effects on cancer cells during treatment. Partial data on the effect of ascorbic acid on fibroblasts indicate that it may also modulate collagen secretion in CAFs and impart tumor-suppressive effects. Thus, future studies should verify the effect of ascorbic acid on CAFs. The findings of this review can be used to guide further research and clinical trials.